Educational Assessment in Portugal - Fernandes, Domingos (2012)
This paper discusses some of the Portuguese education features and its intended learning assessment system. Pupils’ retention and drop out rates are analysed and discussed. Three characteristics of the intended assessment system are presented and discussed in this paper: a) the predominance of formative assessment; b) the predominance of internal assessment; and c) student retention decisions made at the end of basic schooling cycles. Some features of both internal and external assessments are also analysed and discussed. Generally speaking the Portuguese assessment system can be seen as appropriate and progressive. However, there still exists a significant gap between what has been legally proposed and the so-called “real system”. Thus, some recommendations are made aimed at reducing or eliminating that gap which is seen as one of the greatest challenges to be faced by Portuguese society in the years to come